Chemical Structure Profile and Computational Descriptors of Fenbufen Butanamine by PubChem - Yuneka Saristiana; Fendy Prasetyawan; Ratna Mildawati; Yogi Bhakti Marhenta; Eka Hayati Rhomah; Mujtahid Bin Abd Kadir (Jurnal Kajian dan Inovasi Ilmu (JKII), 2025)
Fenbufen Butanamine is a structural derivative of the non-steroidal anti-inflammatory drug (NSAID) Fenbufen, characterized by the addition of a butanamine group to its core structure. This modification is intended to improve the pharmacokinetic and pharmacodynamic properties of the parent compound, potentially enhancing its therapeutic efficacy. In this study, we conducted a detailed computational analysis of Fenbufen Butanamine’s chemical structure and molecular descriptors using data retrieved from the PubChem database. The chemical identity was confirmed by its IUPAC name, InChI, InChIKey, and SMILES notation, which provide precise molecular characterization essential for database referencing and further computational modeling. Key computational descriptors, such as molecular weight, logP, topological polar surface area (TPSA), and the count of hydrogen bond donors and acceptors, were analyzed to assess drug-likeness and predict pharmacokinetic behavior. Our findings indicate that Fenbufen Butanamine possesses a biphenyl core that contributes to hydrophobic interactions, while the butanamine side chain introduces hydrophilic properties. This amphiphilic nature is likely to influence the compound’s solubility, membrane permeability, and binding affinity to biological targets. The computed descriptors suggest favorable properties for oral bioavailability and potential interactions within biological systems. These results serve as a foundational step for in silico drug design and optimization of Fenbufen derivatives. Further experimental and pharmacological studies are warranted to validate these computational predictions and explore the therapeutic potential of Fenbufen Butanamine.